2013
DOI: 10.3402/ljm.v8i0.22520
|View full text |Cite
|
Sign up to set email alerts
|

Rose geranium essential oil as a source of new and safe anti-inflammatory drugs

Abstract: BackgroundSince the available anti-inflammatory drugs exert an extensive variety of side effects, the search for new anti-inflammatory agents has been a priority of pharmaceutical industries.AimsThe aim of the present study was to assess the anti-inflammatory activities of the essential oil of rose geranium (RGEO).MethodsThe chemical composition of the RGEO was investigated by gas chromatography. The major components were citronellol (29.13%), geraniol (12.62%), and citronellyl formate (8.06%). In the carragee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 29 publications
5
36
1
2
Order By: Relevance
“…Also, our results are in agreement with a study by Boukhatem et al (21), whose histological analysis revealed that rose-scented geranium oil inhibited the skin inflammatory process in vivo .…”
Section: Resultssupporting
confidence: 94%
“…Also, our results are in agreement with a study by Boukhatem et al (21), whose histological analysis revealed that rose-scented geranium oil inhibited the skin inflammatory process in vivo .…”
Section: Resultssupporting
confidence: 94%
“…However, our results diverge from those published by other studies in which the concentration of geraniol (23-38%) was higher than that of citronellol (21-28%) [15,16]. The chemical composition of geranium oil will depend on a number of factors, including differences in climatic conditions and geographical locations, season at the time of collection, and fertilization [17].…”
Section: Gc Analysiscontrasting
confidence: 99%
“…According to the Sonali Sinha and colleagues' study [43], GE is considered safe for human consumption at low concentrations. In Mohamed Nadjib Boukhatem and colleagues' study [44], essential oil of rose geranium (RGEO), whose major components were citronellol (29.13%), GE (12.62%), and citronellyl formate (8.06%), was administered orally in three different doses to mice, 10, 100, or 1,000 mg/kg and the results indicated that RGEO might have significant potential for the development of novel anti-inflammatory drugs with improved safety profile. Muthukumaran and colleagues' study [45] showed that A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 15 chronically treatment with GE (100 mg/kg) for 12 weeks on animals did not significantly activate the key inflammatory cytokine, NF-κB in liver, heart and aorta tissues.…”
Section: Discussionmentioning
confidence: 99%